THE ROLE OF SHARIA AUDITORS IN ENSUREING COMPLIANCE OF SHARIA FINANCIAL INSTITUTIONS IN SHARIA BANK - Oktavia Saputri; Rio Restu; Siska Asrina (Publikasi Inspirasi Indonesia, 2024)
The current development of sharia banking has encouraged the need for sharia auditors because sharia auditors have a role in sharia compliance. This research aims for sharia auditors to ensure the compliance of sharia financial institutions. This type of research uses a qualitative method, a descriptive approach with literature study data. The results of this research show that ensuring compliance of sharia financial institutions is in accordance with sharia financial concepts. Sharia auditors must have competence in the field of sharia accounting and auditing.